A novel heat transfer model of biomass briquettes based on secondary development in EDEM. (February 2019) - Li, Yudi; Xu, Hongguang; Jing, Chenghu; Jiang, Jihai; Hou, Xuyan
Abstract: Temperature is important to the quality of biomass briquettes in hot-forming. In this paper, a heat transfer model based on plastic deformation was constructed in the EDEM by discrete element method at the grain scale. The prediction performance of the model was validated by comparing the temperature evolution in simulation with the experimental values. The influences of process parameters on heat transfer including the amount of compression, heating temperature, diameter of mold, moisture content and dwell time were discussed. The rate of heat transfer increased with the briquetting conditions of higher compression, higher heating temperature, lower diameter of the mold, higher moisture content and longer dwell time. It is expected that the new heat transfer model will help in getting enhanced briquettes quality in addition to improved utilization of biomass energy such as bio-refinery, biogasification and other biotechnologies. Graphical abstract: Highlights: A novel heat transfer model of biomass briquetting with DEM method was developed. Plastic deformation in briquetting was introduced into the heat transfer model. The simulations of the model were implemented by re-development in EDEM. The effects of several process parameters on heat transfer were analyzed.